Odpowiedź :
Odpowiedź:
[tex]a)\ \ 6\frac{1}{4}-\frac{2}{5}=6\frac{5}{20}-\frac{8}{20}=5\frac{25}{20}-\frac{8}{20}=5\frac{17}{20}\\\\b)\ \ 7\frac{6}{7}+3\frac{4}{5}=7\frac{30}{35}+3\frac{28}{35}=10\frac{58}{35}=11\frac{23}{35}\\\\c)\ \ 10\frac{2}{9}-2\frac{3}{5}=10\frac{10}{45}-2\frac{27}{45}=9\frac{55}{45}-2\frac{27}{45}=7\frac{28}{45}\\\\d)\ \ 8\frac{3}{10}+2\frac{3}{8}=8\frac{12}{40}+2\frac{15}{40}=10\frac{27}{40}[/tex]
[tex]e)\ \ 9\frac{7}{9}+4\frac{4}{7}=9\frac{49}{63}+4\frac{36}{63}=13\frac{85}{63}=14\frac{22}{63}\\\\f)\ \ 8\frac{3}{7}-2\frac{4}{5}=8\frac{15}{35}-2\frac{28}{35}=7\frac{50}{35}-2\frac{28}{35}=5\frac{22}{35}[/tex]